Risky (farm) business: Perceptions of economic risk in farm succession and inheritance. (April 2020) - Leonard, Brian; Farrell, Maura; Mahon, Marie; Kinsella, Anne; O'Donoghue, Cathal
Highlights: Generational renewal is high on the political agenda for agriculture, with young farmers linked to positive outcomes. There are limited policy incentives for older farmers to consider engaging in the farm succession and inheritance process. Farmers perceive risks and uncertainties regarding the transfer process, and thus avoid handing over to their successors. Taxation, retirement income, long term care cost, and marital breakdown are motivations for farmers to retain ownership. Financial incentives related to generational renewal must aim to alleviate the level of risk perceived by farmers.